The Effect of Kinesio Taping in Reducing Myofascial Pain Syndrome on the Upper Trapezius Muscle: A Systematic Review and Meta-Analysis - Mansour Alotaibi; Abdulraouf Ayoub; Theodore King; Shadab Uddin (European Scientific Journal, ESJ, 2018)
Background: Myofascial Pain Syndrome is a condition causing pain at myofascial trigger points. Kinesio Taping has been widely used to decrease pain and improve range of motion. Objective: The purpose of this systematic review and meta-analysis was to evaluate the effectiveness of therapeutic programs that include kinesio taping on reducing myofascial pain syndrome symptoms. Methods: Independent research was performed for legit studies using the following electronic databases: PubMed, CINAHL, MEDLINE, SPORT Discus, EM base, and Cochrane Central Register of Controlled Trials, from February 2017 to March 2017. The keywords were “keniso tape myofascial” AND “taping myofascial” AND “myofascial pain Syndrome” AND “myofascial trigger points.” The research resulted in 5,793 articles that eventually included 6 articles that had met the inclusion and exclusion criteria, and the data extracted data from the articles was about the pain severity, and was measured by Visual Analog Scale (VAS). Results: The collected data was pooled from the results of 256 subjects (199 females and 57 males). Using KT showed improvement but not significant statistically in three of the analyzed studies, and the remaining three studies showed a statistical significant reduction in VAS score. The overall P value that computed by the European Scientific Journal February 2018 edition Vol.14, No.6 ISSN: 1857 – 7881 (Print) e - ISSN 1857- 7431 337 Comprehensive Meta-Analysis 2.0 software was statistically significant (P value= 0.001) between the KT group and the control group. Conclusion: This systematic review and meta-analysis was performed on six studies in regarding to the efficacy of KT on the myofascial pain in the upper trapezius muscle. The meta-analysis suggests KT with other therapeutic protocols to treat myofascial pain syndrome and increase cervical range of motion as well as the functional activities.